« Déceler l’accord entre parties dans les procès pour dette : un exemple de justice négociée à la fin du xvie siècle au tribunal des échevins de Nancy » - Jonathan Pezzetta (Criminocorpus)
Negotiation played a central role in the resolution of disputes during the Ancien Régime. Parties' attempts to reach an agreement often begin before the judicial authorities are convened. During a trial, the negociations are carried on outside the courtroom. The end of the negotiations generally closes the case, hence a very high evaporation rate. Paradoxically, even though negotiations are constant during litigation, only few traces are left in the judicial sources. This is particularly true for documents like the “registers of the causes” of the court of the aldermen of Nancy, a sovereign court located in the heart of the duchy of Lorraine’s capital. These registers, extending from the sixteenth to the beginning of the seventeenth centuries, contain all the civil cases judged annually by the aldermen. One register stands out from the others: the "register of contredits" for the years 1597 and 1598: this register contains only cases of seizure and large debts. This article assumes that the reciprocal interests between creditors and debtors in these cases give them more reason to reach a consensus and to negotiate than ?. The present study aims at establishing a protocol to study this particular source and thus find traces of agreements.